DEVELOPING METHOD OF TEACHING ‘INFORMATION LITERACY IN TIMES OF DISASTER’ IN JAPANESE LANGUAGE TEACHING - Akiko Honda (STBA LIA - Jakarta, 2018)
This paper discusses the need for education in ‘Information Literacy in Times of Disaster’ in Japanese language education for non-native speakers of Japanese who are staying in Japan. ‘Information Literacy in Times of Disaster’ refers to the ability to obtain necessary information and transmit it as appropriate in the circumstances when a major natural disaster occurs, such as an earthquake. After the April 2016 Kumamoto earthquake, the author investigated the behavior of international students when the earthquake occurred, the criteria for their decisions, their means of collecting information and other matters. The results revealed the issue that international students’ behavior frequently relied on others’ words and they could not make decisionsindependently. The factors causing these issues include: (1) lack of knowledge and understanding of Japanese language and Japanese society; (2) psychological distance from information in Japanese; and (3) capacity to analyze information. This report proposes the development of methods of teaching ‘Information Literacy in Times of Disaster’ to resolve these issues and discusses how the development of these teaching methods will contribute to furthering information literacy education in Japanese languageeducation.